An Evaluation of Status and Output of “Deliberative Rationality “in Rawls’ Theory of Justice - Seyed Ali Mahmoudi (رهیافتهای سیاسی و بین المللی)
The foundation of John Rawls’ theory of justice is how to choose two principles of justice in a manner that the parties of dialogue reduce the level of their mistakes at least possible in their choices. Biased upon the theoretical principles in rational choices, deliberative rationality in particular, and also choosing constructivism- contrary to teleological and intuitional approaches which circumscribe options in the realm of right- Rawls makes an attempt to open path to a rational choice. Hence, rational, free and equal persons, choose the principles of justice through a considered dialogue with each other, and also with their yokefellows. In this research, I have used the methodology of conceptual analysis and critical evaluation on the basis of analytical philosophy. In this article, the core of the argument is that how and in which manner, Rawls’ deliberative rationality ends to an agreement among citizens. After the assessment of above-mentioned principle, the deliberative rationality in particular to attain a choice, the outcome of the research is access of citizens to agreement through thoughtful dialogue in order to solve macro social and political problems. In this regard, Rawls’ logical and well-organized theory as a strong philosophical support, increases the capacities and possibilities of effective dialogue, and eventually possible achievement to common fundamental agreements.